Extraction of free fatty acids from wet Nannochloropsis gaditana biomass for biodiesel production. (March 2015) - Hita Peña, Estrella; Robles Medina, Alfonso; Jiménez Callejón, María J.; Macías Sánchez, María D.; Esteban Cerdán, Luis; González Moreno, Pedro A.; Molina Grima, Emilio
Abstract: The objective of this work is to develop a process for producing biodiesel from the saponifiable lipid (SL) fraction of the wet microalgal biomass Nannochloropsis gaditana . The method consists of five steps. Firstly, crude fatty acid salt extraction was carried out using a KOH-ethanol (96%) solution, which allows one to extract the SLs as potassium salts. This transformation permits better separation of the unsaponifiable lipids (the second step) and finally produces purer biodiesel. The unsaponifiable lipids were then separated with hexane, after establishing the ethanol-water solution water content at 30% w/w. Some unsaponifiable lipids (carotenoids and phytosterols) are products of interest that might be purified from this fraction thus helping to improve the process's profitability. Thirdly, free fatty acids (FFAs) were purified by acidification of the ethanol-water solution to pH 5 and were then extracted with hexane. Fourthly, the FFAs were transformed to biodiesel by esterification with excess of methanol catalyzed using sulphuric acid, removing the excess by washing with hot water. Under these conditions the biodiesel purity and yield were 74.8% and 82% w/w, respectively. Finally, the biodiesel was clarified/purified up to 96.5% purity by adsorption with bentonite. The final biodiesel yield was 80.9%. Highlights: Biodiesel production from free fatty acids extracted from wet microalgal biomass. The process allows obtaining 96.5% pure biodiesel, with 80.9% yield. The unsaponifiable fraction, which contains high-value products, was separated. Biodiesel was clarified-purified by adsorption with bentonite. The esterification reaction proves faster than the transesterification reaction.